Impacto da privatização na eficácia organizacional: o caso da Companhia Siderúrgica Nacional - CSN - Toigo, Maristela Aparecida (Universidade do Vale do Rio do Sinos, 2006)
The Brazilian State due to the economic globalization which demands more competitivity and investments in social areas, has caused changes in the management policy of the companies with majority government ownership. The privatization it self has been a strategic answer to the incompatibility between the budget limitations and the necessary investments that are required by the demanding market with the redefinition of the State, the private action has gotten more freedom, competitivity, and has become more efficient when it comes to company management. The metal companies before the privatization had results, obsolete industrial machinery, and not up- to-date technology due to the lack of public resources. This study aims to point out the impact of the privatization in the Companhia Siderurgica Nacional-CSN. There has been a documental research based on a comparative analysis of the accounting demonstrations. As a result, it was possible to realize that the indicators used in this study have showed that negat
Keywords: análise econômico-financeira; eficácia organizacional; siderurgia; privatização; financial and economic analysis; metal company; privatization; Ciências Sociais Aplicadas